Analisis Model Sistem Dinamis pada Penjualan Olahan Buah Alpukat di PT XYZ Menggunakan Software Vensim - Mukhammad Rivaldi Ghani; Joumil Aidil Saifuddin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The rapid development of the industry has driven the emergence of various technologies that can support the industry, especially in production activities. Production activities are the actions performed by humans to generate a product, be it goods or services, which are then utilized by consumers. These activities operate around the clock to produce products that meet market demand. For smooth production activities, manufacturing industries need to provide raw materials that meet targets and create plans before operating, with inventory levels set to ensure that needs are met in terms of quality, quantity, time, and low cost as planned. PT XYZ is a fruit juice manufacturer with avocado juice being its most popular product. The production of avocado juice was analyzed over the period of 2015-2020 using Vensim software with four scenarios to assess the availability of raw materials. The research findings reveal that the total availability of flour raw materials in 2020 was 10,000 tons; 9,450 tons; 9,500 tons; 10,150 tons; 11,400 tons; 13,250 tons. To address the issue, PT XYZ can monitor fruit stocks and periodically estimate fruit seasons.